VULNERABILITY ASSESSMENT AT MT. BROMO INDONESIA BY USING TIME-SERIES LAND SURFACE DEFORMATION AND GIS - Arbad, Arliandy P.; Takeuchi, W.; Aoki, Y.; Ardy, Ahmad (POLITEKNIK NEGERI JAKARTA, 2019)
Among the 127 active volcanoes located in eastern Java, Indonesia. Mt. Bromo is the most famous active volcano, type of Mt. Bromo is a strombolian. Many aspects that make volcano an interesting, we conduct a critical and comprehensive study and analysis concerning of volcano eruption based on remote sensing and GIS approaches. Nowadays, remote sensing play an important role to observe volcanic activity and facilitate real-time information. The method used in this study is the determination level of risk in the Mt. Bromo by Pairwise Comparison method. Vulnerability parameters to be obtained from the potential of land deformation, population density, and distance from the volcano dome. In addition, we used SAR data to observe time-series land surface deformation which derived from PALSAR sensor and the images which L-band frequency characteristic on board from Advanced Land Observing Satellite (ALOS) with active microwave sensor to achieve cloud-free and day-and-night land observation. The dataset is composed of 24 SAR images, collected from 24 May 2007 to 5 July 2016 (Descending passes, HH polarization). Consequently, the information result has been created and processed at a municipal or city level including thematic maps, the database has been built, classified and analyzed by using GIS environment. The main idea is providing hazard mitigation map at Mt. Bromo to provide adequate guidance for disaster-prone areas to determine the level of disaster risk.